Effect of engine parameters, combustion and emission characteristics of diesel engine with dual fuel operation. (15th October 2021) - Antony Casmir Jayaseelan, G.; Anderson, A.; Manigandan, Sekar; Elfasakhany, Ashraf; Dhinakaran, Veeman
Highlights: Biodiesels of Candle nut oil and Soap nut oil is prepared by transesterification process. Optimum mixture of combined biodiesel is prepared with high oxidation stability and good CFPP. 10% of Candle nut and 90% of soap nut biodiesel mixture indicated optimum results. Engine performance and emission behavior of combined biodiesel fueled engine is determined. Decreased level of hydrocarbons and carbon monoxide was measured in the engine by using combined biodiesel. Abstract: Candle nut oil was produced from candle nut seeds by the process of crushing and filtering. The candle nut biodiesel was prepared by a two-step co-solvent esterification process and is found to be one of the best alternate fuels for running the diesel engine. The oxidation stability of the candle nut biodiesel was found to be poor and this leads to high acid value and inception of insoluble gums and dregs or scum that can block the fuel filters. Soap nut oil was extracted from soap nut seeds by the process of crushing and filtering. The soap nut biodiesel was prepared by transesterification process and has higher oxidation stability compared to candle nut biodiesel. Similarly, the cold filter plugging point of candle nut biodiesel is good compared to soap nut biodiesel and it depends upon the amount of saturated fat. Hence the mixing of soap nut biodiesel and candle nut biodiesel will increase the properties for the smooth run of engine with fewer emissions compared to diesel. In this work, engine performances and exhaust contents were evaluated for various blends of mixed soap nut biodiesel and candle nut biodiesel.